Tanaidáceos brasileiros da subordem Monokorophora (Crustacea) - Brum, Iva Nilce da Silva (1978)
Eights species of Tanaidacea suborder Monokonophora, known up to date from Brazilian littoral, are studied Theses species are distributed in five genera and four families Paraleiopus macrochelis n.g. and n.sp. is established for specimens collected in Santa Cruz, littoral of the State of Espírito Santo. Remarks are made on the importance of the morphological features employed, for distinction of the families and genera, which shows to be necessary to undertake a better systematic arrangement. Definitions of the four families and the five genera are given, as well as keys, data on the geographical range and descriptions with illustrations of each species. Due to the diversity of points of view of several carcinologists on the nomenclature of Tagmas and appendages of the body, the terminology adopted by WOLFF (1965) was followed.